Partimento and continuo playing in theory and in practice - Christensen, Thomas Street; Moelants, Dirk, 1946-; Snyers, Kathleen (Collected writings of the Orpheus Institute, 2010)
This volume is a collection of essays based on lectures given at the International Orpheus Academy for Music Theory on 'Music and Theory: Thoroughbass in Practice, Theory, and Improvisation''. Hence the point of departure was not 'Music Theory'' as such, but the interaction between music theory, music history, performance practice, aesthetics, and related sciences. This multidisciplinary approach, with the accent on the interplay between music performance and music theory, is reflected in the contributions to this book. Thomas Christensen, in his contribution, shows how the development of tonal.